Indecisive Between The Margin And The Center - Hidouci, Sarah; Kheladi ,Mohammed (University of Eloued جامعة الوادي, 2024)
Abstract: This study aims to analyze Buchi Emecheta's The New Tribe through exploring themes of diaspora and displacement and shedding the light on the characters' experiences both within and outside their country of origin by having a harmony of two different cultures; one that is conventional and another that is contemporary. Through a postcolonial lens, we examine how Emecheta's work offers a fresh outlook on the challenges of displacement, belonging, and selfformation in the postcolonial world highlighting the significance of Emecheta's contributions to the study of diaspora and alienation, offering insights into cultural assimilation and navigating diverse societies.
Aspects Of Diaspora And The Question Of Unbelonging In Buchi Emecheta’s The New Tribe
Keywords: Diaspora; Postcolonialism; Exile; Identity